2015
DOI: 10.1080/21681015.2015.1071288
|View full text |Cite
|
Sign up to set email alerts
|

Trade-in strategy for a durable goods firm with recovery cost

Abstract: This study deals with the trade-in rebates offered by the manufacturer to the consumers. We investigate when and how a durable goods firm should offer a trade-in rebate to collect and recover used products, in order to achieve better price discrimination and weaken competition from third-party remanufacturers. It creates segment effect by offering different prices to different groups of customers. This study determines the optimal pricing and/or trade-in rebate, and examines the strategic choice among the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Trade-in incentives can be offered in two distinct forms: immediate credits or discounts to be redeemed on new product purchases [60][61][62]. The literature on trade-in policies is expansive in both economics and closed-loop supply chain management [6,63]. Researchers addressed many issues involved in product take-back acquisition decisions: the existence of a secondary market in monopolistic firms [7]; competition between OEMs and remanufacturers in monopoly markets [6,64,65] or duopoly ecosystems [66][67][68][69]; the comparison between trade-ins and different marketing strategies [7,70,71]; the trade-off between online or offline platforms [72,73]; the analysis of buyback and discounts programs [62]; and the optimal rebate decision in business-to-consumer foundation [74][75][76].…”
Section: Trade-in Policymakingmentioning
confidence: 99%
“…Trade-in incentives can be offered in two distinct forms: immediate credits or discounts to be redeemed on new product purchases [60][61][62]. The literature on trade-in policies is expansive in both economics and closed-loop supply chain management [6,63]. Researchers addressed many issues involved in product take-back acquisition decisions: the existence of a secondary market in monopolistic firms [7]; competition between OEMs and remanufacturers in monopoly markets [6,64,65] or duopoly ecosystems [66][67][68][69]; the comparison between trade-ins and different marketing strategies [7,70,71]; the trade-off between online or offline platforms [72,73]; the analysis of buyback and discounts programs [62]; and the optimal rebate decision in business-to-consumer foundation [74][75][76].…”
Section: Trade-in Policymakingmentioning
confidence: 99%
“…By considering the interaction between "forwardlooking" consumers and enterprises and the heterogeneity of market consumers, we found that forward-looking consumers are willing to pay higher prices than the value of products. Chen [30] further proposed that when considering strategic consumers, whether enterprises would carry out the trade-in depends on the price and characteristics of the new product, and proposed that the depreciation rate will increase with the increase of the depreciation rate of the used product, but decreases with the increase of consumer's willingness to exchange the old for the new products.…”
Section: Research On Discount and Pricing Of Trade-in Activitiesmentioning
confidence: 99%
“…Agrawal [31] studied the impact of trade-in preferences on price discrimination, established a bargaining model between manufacturers and recyclers, and finally coordinated the price issue between them by providing trade-in services, and proposed that an enterprise can achieve perfect price discrimination by using trade-in preferences. Ray [32] studied how firms can provide optimal service strategies to replace old products with new ones under the assumption that durable goods technology is relatively stable. They found that changes in trade-in rebate were affected by factors such as the durability and depreciation rate of used products.…”
Section: Research On Discount and Pricing Of Trade-in Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their research, Li et al [15] developed a two-period closed-loop supply chain model, considering the influence of a secondary market, where the OEM can sell its remanufactured products. The literature about the trade-in program mainly discuss the role of a trade-in strategy stimulating market demand, reducing resource waste, and improving the total social welfare [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%